Tumor Suppressor WWOX and p53 Alterations and Drug Resistance in Glioblastomas - Chiang, Ming-Fu; Chou, Pei-Yi; Wang, Wan-Jen; Sze, Chun-I; Chang, Nan-Shan (Frontiers in Oncology, 2013)
Tumor suppressor p53 are frequently mutated in glioblastomas (GBMs) and appears to contribute, in part, to resistance to temozolomide and therapeutic drugs. WW domain-containing oxidoreductase WWOX (FOR or WOX1) is a proapoptotic protein and is considered as a tumor suppressor. Loss of WWOX gene expression is frequently seen in malignant cancer cells due to promoter hypermethylation, genetic alterations, and translational blockade. Intriguingly, ectopic expression of wild type WWOX preferentially induces apoptosis in human glioblastoma cells harboring mutant p53. WWOX is known to physically bind and stabilize wild type p53. Here, we provide an overview for the updated knowledge in p53 and WWOX, and postulate a potential scenarios that wild type and mutant p53, or isoforms, modulate the apoptotic function of WWOX. We propose that triggering WWOX activation by therapeutic drugs under p53 functional deficiency is needed to overcome TMZ resistance and induce GBM cell death.